The Influence of PBL Learning Model on High School Students' Learning Outcomes in System of Linear Equations in Three Variables Material - Dewi, Yolanda Pradinata Citra; Anas, Aswar; Lutfiyah, Lutfiyah (Education and Talent Development Center Indonesia (ETDC Indonesia), 2025)
This study aims to determine how the application of the problem-based learning model affects the learning outcomes of class X students regarding the material on systems of linear inequalities in three variables. This research is a pre-experimental one-group pretest-posttest design, with class X research subjects at Al-Hidayah Islamic High School. The instrument used is a validated system of linear inequalities in a three-variable material understanding test. The analyses used in this study are descriptive and inferential. The study found a big improvement in learning results after using the problem-based learning (PBL) method for the System of Linear Inequalities in Three Variables material, with an average score of 46.0833 before the test and 75.6667 after. The significant value of the hypothesis test is below 0.05, which means 0.00 < 0.05; thus, H0 is rejected and H1 is accepted. This study shows a significant difference in student learning outcomes when using the Problem-Based Learning (PBL) learning model.